2015
DOI: 10.7205/milmed-d-14-00187
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Influence of Mild Traumatic Brain Injury and Posttraumatic Stress Disorder on Alcohol Use Disorder in OEF/OIF Veterans

Abstract: Findings from this study can inform treatment providers by alerting them to the possibility of subthreshold PTSD in Veterans with mTBI. Providers may begin PTSD treatments or consider targeting hyperarousal symptoms early in treatment to reduce distress. PTSD is also uniquely associated with alcohol use disorder in male Veterans, while more research on predictors of alcohol use disorder is needed for female Veterans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…It should be taken into consideration that some recent studies have not found that TBI increases risk for AUD [2,15]. Most recently, Miles and colleagues (2015) found that mTBI did not predict AUD diagnoses for men or women veterans [15]. This study improved on the Miller and Johnson studies by using a mental health evaluation instead of ICD-9 codes for diagnoses, but the sample size was smaller (N=1278).…”
Section: Dual Nature Of Aud and Tbi Riskmentioning
confidence: 87%
See 3 more Smart Citations
“…It should be taken into consideration that some recent studies have not found that TBI increases risk for AUD [2,15]. Most recently, Miles and colleagues (2015) found that mTBI did not predict AUD diagnoses for men or women veterans [15]. This study improved on the Miller and Johnson studies by using a mental health evaluation instead of ICD-9 codes for diagnoses, but the sample size was smaller (N=1278).…”
Section: Dual Nature Of Aud and Tbi Riskmentioning
confidence: 87%
“…This increased risk is independent of TBI severity, and those incurring a TBI outside of deployment may be at greater risk. It should be taken into consideration that some recent studies have not found that TBI increases risk for AUD [2,15]. Most recently, Miles and colleagues (2015) found that mTBI did not predict AUD diagnoses for men or women veterans [15].…”
Section: Dual Nature Of Aud and Tbi Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…TBI is caused by a blow, bump, or jolt to the head and is diagnosed by severity ranging from mild to severe (Centers for Disease Control and Prevention, 2017). Symptoms of TBI vary and may include physical symptoms (e.g., headache, trouble sleeping, vision problems, noise and light sensitivity, and feeling dizzy), cognitive symptoms (e.g., memory problems, difficulty staying focused, poor judgment, trouble putting thoughts together), and/or emotional symptoms (e.g., depression, anger, outbursts, anxiety, and personality changes) (Miles, Graham, & Teng, 2015; U.S. Department of Veterans Affairs, 2015; U.S. Department of Veterans Affairs, 2017). PTSD frequently accompanies TBI (Gironda et al, 2009;Hoge et al, 2008;Ruff, Riechers, Wang, Piero, & Ruff, 2012).…”
mentioning
confidence: 99%